What is my walking neighbourhood? A pilot study of English adults' definitions of their local walking neighbourhoods - Smith, G; Gidlow, C; Davey, R; Foster, C (2010)
Background: Existing measures of perceptions of the environment associated with walking commonly rely on providing a definition of 'neighbourhood', e.g. 1 mile area around the home. We have little understanding of how these examples relate with adults' own geographical definitions of their neighbourhood area. Our pilot study examined the congruence between definitions used in environmental questionnaires and adults' own definitions of neighbourhood.Methods: We conducted 58 face-to-face interviews with participants randomly selected from 10 areas of Stoke-on-Trent, England. Participants were shown printed maps showing their local area with road names and places of interest (e.g. shops, services, green space) and were asked: (i) to recall usual walking destinations (from their home); (ii) to draw their 'neighbourhood walking area' on the map. Annotated maps were scanned back into GIS for analysis.Results: When asked to draw their 'neighbourhood' boundary, the resulting area drawn by participants on average represented only 16 ± 20% of the commonly used total straight-line buffer of 1 mile (or 1.6 km) with a range of 0.3% to 111%. Even when repeated using a network buffer (rather than straight-line) the same comparison resulted in a mean of 36% (± 47%) and a range of 0.6 to 245%.Conclusions: We found that adults' interpretation of their neighbourhood area does not appear to relate accurately to the definitions typically used in research into environmental perceptions and walking. This mis-match warrants further investigation as definitions used in existing measures may be consistently misclassifying perceived local walking neighbourhoods. © 2010 Smith et al; licensee BioMed Central Ltd.